Historical dictionary of Judaism - Solomon, Norman, 1933- (Historical dictionaries of religions, philosophies, and movements., 2015)
"This third edition of Historical Dictionary of Judaism covers the history of the Jewish religion, ranging from its biblical roots, through its formulation in the era of the Talmud, to the present day. This collection covers the development of Judaism in the medieval Christian and Islamic worlds, its varied responses to Enlightenment and modernity, the creation of new philosophies of Judaism in the wake of the Holocaust, and the establishment of the State of Israel, and contemporary issues such as feminism, secularism, and the ethics of war and medicine. This is done through a chronology, an introductory essay, appendixes, and an extensive bibliography. The dictionary section has over 800 cross-referenced entries on important personalities in Jewish religious history, including biblical personalities with an emphasis on how they are understood in Jewish, Christian, and Islamic tradition. This book is an excellent access point for students, researchers, and anyone wanting to know more about Judaism."--Publisher's description